Development of Prunus salicina cuttings grafted in situ in different susbtrates containing lombrihumus. - Gónzalez-Castellanos, Anacleto (2011)
The objective of this study was to determine the effect ofsubstrates with lombrihumus on the development of plumbcuttings growing in a nursery. Sections of Prunus salicina var.Mariana 2624 were grafted on con P. salicina var. Methleyand planted on substrates containing lombrihumus. Thework was conducted at the Faculty of Agricultural Sciences,UNAM, México, under fi eld conditions, from December2002 to January 2003. A completely randomized wasemployed, with factorial arrangement with four treatmentsand four replications. The factors studied were the time ofcutting and grafting and the different types of substrates.The variables measured were plant length, cutting diameter,number of internodes, percent successful grafting, number ofleaves per plant, leaf area, perimeter and length. The opticaltime for cutting preparation and grafting in situ under fi eldconditions in Toluca, México, was January. The largestgrafting success was obtained with susbtrate composed of20% peat (azolve soil), 30% perlite, and 50% lombrihumus.With this technology, fully developed plumb plants can beobtained in nine months.